The Effectiveness of Montessori Approach on Independence and Cognitive Abilities of Early Childhood Children in the Digital Era - Kholifatur Rizkiyah, Nur (Generasi, 2024)
Background: The Montessori approach emphasizes child-centered learning, yet its effectiveness in the digital era remains underexplored. This study examined Montessori education's impact on independence and cognitive development, with digital media exposure as a moderating factor. Methods: A 16-week quasi-experimental study with propensity score matching included 156 children aged 4-6 years (Montessori: n=78; Control: n=78). Independence and cognitive abilities were assessed using validated instruments. Digital media exposure was tracked via parent-reported weekly questionnaires. Results: Montessori children showed significantly greater improvements in independence (d=0.58, p<.001) and cognitive abilities (d=0.53, p<.001). Independence gains were strongest in domestic and personal care domains. Cognitive advantages appeared most in planning (np²=.086) and learning abilities (np²=.061). Digital media exposure significantly moderated the independence relationship (b=-0.42, p=.009), with Montessori advantages diminishing above 23.4 hours weekly screen time. Conclusions: Montessori education effectively promotes early childhood development. However, extensive digital exposure attenuates these benefits, necessitating balanced technology integration strategies.